CONTENT OF THE SCIENCE CURRICULUM FOR CHILDREN WITH PROBLEMS IN MENTAL DEVELOPMENT AND REQUIREMENTS FOR STUDENTS' EDUCATION (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The article highlights the content of the natural science curriculum for children with intellectual development disorders and the requirements for students’ knowledge in this process. The pedagogical foundations of organizing the educational process are presented, taking into account students’ individual abilities, as well as their perception, memory, and thinking characteristics.